Influencing parameters in the electrochemical anodization of TiO2 nanotubes: Systematic review and meta-analysis. Issue 14 (15th July 2022) - Puga, M.L.; Venturini, J.; ten Caten, C.S.; Bergmann, C.P.
Abstract: Comprehensive control of processing techniques is primordial when fine-tuning the morphological features of titanium dioxide nanotube arrays (TNTs). This systematic review and meta-analysis compiled articles published from 2007 to date on the synthesis and growth mechanism of nanotubes fabricated via electrochemical anodization and evaluated the potential relationships between anodizing conditions and the resulting structures. Studies were gathered from the Science Direct online database, screened according to predefined criteria, and evaluated for their eligibility. Ninety-nine studies were assessed in the meta-analysis, 87 of them on tube length, 80 on tube diameter, and 33 on wall thickness. Multiple linear regression was performed to test if anodization parameters significantly predicted the resulting morphology of TiO2 nanotubular structures. Overall regression for the three responses was statistically significant (length: R 2  = 0.487, p < 0.001; diameter: R 2  = 0.899, p < 0.001; wall thickness: R 2  = 0.792, p < 0.001). Applied potential was one of the main effects predicting all three responses (p < 0.001 in every model). Other important main predictors were anodizing time for tube length (p < 0.001), water percentage for tube diameter (p < 0.001) and ammonium fluoride (NH4 F) concentration for wall thickness (p < 0.001).